Artificial Intelligence, School Supervision and School Plant Management in Public Secondary Schools in Abuja, Nigeria - Chogwu, Benjamin Dorcas; Daniel, Adi (International Journal of Global Sustainable Research, 2024)
The aim of this research was to evaluate how artificial intelligence affects the supervision of schools and the management of school facilities in public secondary schools within the Federal Capital Territory, Abuja, Nigeria. The study utilized a descriptive survey approach, targeting all 292 public senior secondary schools in Abuja. A sample of 400 principals and vice principals was selected using a stratified random sampling method. The research utilized a questionnaire titled "Artificial Intelligence and School Supervision and School Plant Management Questionnaire (AISSSPMQ)" employing a four-point rating scale: (a) strongly agree (S.A) – 4, (b) agree (A) – 3, (c) disagree (D) – 2, and (d) strongly disagree (S.D) – 1. The questionnaire's validity was confirmed by three lecturers from the Department of Educational Management, University of Abuja, and its reliability was assessed using Cronbach Alpha reliability coefficient, yielding a coefficient of 0.87. Data analysis employed Pearson Product Moment Correlation (t-test) at a significance level of 0.05. The study concluded that there exists a significant correlation between artificial intelligence and effective school supervision, as well as between artificial intelligence and effective school plant management in public secondary schools in the FCT, Abuja, Nigeria.